The prevalence of pouch fistulas in ulcerative colitis following restorative proctocolectomy: a systematic review and meta-analysis - Sheng Wei Lo; Ishaan Dharia; Danujan Sriranganathan; Maia Kayal; Edward L. Barnes; Jonathan P. Segal (Intestinal Research)
Background/Aims One complication of restorative proctocolectomy with ileo-anal pouch anastomosis is fistula formation in the pouch. Fistulas can be associated with significant morbidity and pouch failure. We conducted a systematic review with meta- analysis to try and understand the prevalence of pouch fistulas in patients with ulcerative colitis following restorative proctocolectomy. Methods The Embase, Embase Classic, and PubMed databases were searched between January 1979 and April 2022. Studies were included if there were cross-sectional, case-controlled, population-based or cohort studies reporting on prevalence of pouch fistulas in ulcerative colitis. Studies had to report the number of patients with pouch fistulas using either clinical, endoscopic, or radiological diagnosis in an adult population. Results Thirty-three studies screened met the inclusion criteria. The pooled prevalence of developing at least 1 fistula was 0.05 (95% confidence interval [CI], 0.04–0.07). The pooled prevalence of pouch failure in patients with pouch fistula was found to be 0.24 (95% CI, 0.19–0.30). The pooled prevalence of developing a pouch fistula at 3 years, 5 years and more than 5 years was 0.04 (95% CI, 0.02–0.07), 0.05 (95% CI, 0.02–0.07), and 0.05 (95% CI, 0.02–0.10), respectively. Conclusions This is the first systematic review and meta-analysis to report the prevalence of pouch fistula. It also provides a pooled prevalence of pouch failure in these patients. These results can help to shape future guidelines, power future studies, and help counsel patients.